2005
DOI: 10.1529/biophysj.105.066670
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Dynamics in Interphase Cells Revealed by Tracking in a Two-Photon Excitation Microscope

Abstract: Increasing evidence points to a dynamical compartmentalization of the cell nucleus, yet the mechanisms by which interphase chromatin moves and is positioned within nuclei remain unclear. Here, we study the dynamics of chromatin in vivo applying a novel particle-tracking method in a two-photon microscope that provides approximately 10-fold higher spatial and temporal resolutions than previous measurements. We followed the motion of a chromatin sequence containing a lac-operator repeat in cells stably expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
170
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(197 citation statements)
references
References 37 publications
18
170
0
Order By: Relevance
“…Overall, despite of some technical intricacies, we conclude that our results are consistent across conditions, strains, laboratories and devices used to perform the experiment, indicating that the observed rapid chromosomal motions are not the product of artefacts. Similar long-range directed motions have also been reported in eukaryotes 26,27 .…”
Section: Discussionsupporting
confidence: 85%
“…Overall, despite of some technical intricacies, we conclude that our results are consistent across conditions, strains, laboratories and devices used to perform the experiment, indicating that the observed rapid chromosomal motions are not the product of artefacts. Similar long-range directed motions have also been reported in eukaryotes 26,27 .…”
Section: Discussionsupporting
confidence: 85%
“…Interphase chromosomes are highly dynamic, with active chromatin in an open conformation and undergoing continual exchange of protein components , Phair & Misteli 2000. Chromosomal loci are known to be mobile (Marshall et al 1997, Bystricky et al 2004, Levi et al 2005, and recently it has been shown that gene positioning affects gene expression (Brickner & Walter 2004, Ahmed & Brickner 2007, Akhtar & Gasser 2007, Lanctot et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome visualization in vivo gives insight into chromatin dynamics at large length scales (Belmont, 2003;Levi et al, 2005) but is as yet unable to reveal events at the scale of individual nucleosome displacements. A complementary approach is to study individual chromatin fibers by using micromanipulation (Cui and Bustamante, 2000;Ladoux et al, 2000;Bennink et al, 2001;Brower-Toland et al, 2002;Leuba et al, 2003;Claudet et al, 2005;Gemmen et al, 2005;Bancaud et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The processive nature of these activities, and the necessity to disrupt histone-DNA contacts to accomplish them, suggests that chromatin must be dynamic in its structure, with actively transcribing genes perhaps in a continual state of structural rearrangement. The simplest example of chromatin rearrangement that would allow base pair access is displacement or dissociation of part or all of the histone octamer (Felsenfeld, 1996).Chromosome visualization in vivo gives insight into chromatin dynamics at large length scales (Belmont, 2003;Levi et al, 2005) but is as yet unable to reveal events at the scale of individual nucleosome displacements. A complementary approach is to study individual chromatin fibers by using micromanipulation (Cui and Bustamante, 2000;Ladoux et al, 2000;Bennink et al, 2001;Brower-Toland et al, 2002;Leuba et al, 2003;Claudet et al, 2005;Gemmen et al, 2005;Bancaud et al, 2006).…”
mentioning
confidence: 99%